Aerosolterapia y su influencia en el tratamiento de asma bronquial en pacientes menores de 10 años del Hospital Jaime Roldos Aguilera de la ciudad de Ventanas durante octubre 2018 – abril 2019 - Garcia Maldonado, Ambar Ivonne (2019)
Bronchial asthma is considered one of the most common respiratory diseases but it has a great impact on people's health. It generally affects people of all ages, from children to older adults. Different Latin American countries state that both Morbidity and mortality data are increasing, although most cases are due to the presence of different factors. This research project has as direct beneficiaries under 10 years since they are the ones who suffer the ravages of this disease and that until now has not been eradicated, it has only been possible to reduce the symptoms through pharmacological treatments, giving a devaluation to the use of aerosol therapy as an essential treatment in this disease. The main objective of this research is to: Determine the influence of aerosol therapy in the treatment of bronchial asthma in patients younger than 10 years Jaime Roldos Aguilera Hospital Windows city The methods used are Deductive, Analytical, Descriptive Method, among the instruments used we can highlight the following: Interview Guide, Questionnaires, Observation Guide This project has 63 children under 10 years of age who attend Jaime Roldos Aguilera Hospital in the city of Windows, the representative sample is determined by 63 children under 10 years of age since, since it is a finite population, the extraction of the sample is not done, thus working with the number of the population. Within the conclusions of the results of the project we have that the use of aerosolterapia directly influences the improvement of the symptoms of bronchial asthma in children under 10 years who go to the hospital Jaime Roldos Aguilera of the caton Windows and concludes that the majority of complications of bronchial asthma is due to the ignorance of the symptoms of this disease, and it has been shown that through the application of aerosol therapy these symptoms have been disappearing. To solve the aforementioned problem, it is necessary to create a proposal that has the title: Educational program on prevention and outpatient management with aerosol therapy to children under 10 years of age with bronchial asthma. Whose objective is to train mothers and caregivers of children under 10 years of age on the prevention and ambulatory management of Bronchial Asthma